2009
DOI: 10.1007/s11295-009-0216-y
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of population structure in coastal Douglas-fir [Pseudotsuga menziesii (Mirb.) Franco var. menziesii] using allozyme and microsatellite markers

Abstract: Characterizing population structure using neutral markers is an important first step in association genetic studies in order to avoid false associations between phenotypes and genotypes that may arise from nonselective demographic factors. Population structure was studied in a wide sample of ∼1,300 coastal Douglas-fir [Pseudotsuga menziesii (Mirb.) Franco var. menziesii] trees from Washington and Oregon. This sample is being used for association mapping between cold hardiness and phenology phenotypes and singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
30
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 91 publications
6
30
2
Order By: Relevance
“…Population structure and historical demography: The extent of structure among populations of coastal Douglas fir observed at chloroplast and nuclear microsatellites, as well as allozymes, is low and consistent with weak effects of isolation by distance (Li and Adams 1989;Viard et al 2001;Krutovsky et al 2009). We analyzed patterns of differentiation for all 115 polymorphic candidate genes, using pairwise measures of divergence (D xy ) among the six populations, and related this measure to geographical distance using Mantel tests.…”
Section: Methodsmentioning
confidence: 71%
“…Population structure and historical demography: The extent of structure among populations of coastal Douglas fir observed at chloroplast and nuclear microsatellites, as well as allozymes, is low and consistent with weak effects of isolation by distance (Li and Adams 1989;Viard et al 2001;Krutovsky et al 2009). We analyzed patterns of differentiation for all 115 polymorphic candidate genes, using pairwise measures of divergence (D xy ) among the six populations, and related this measure to geographical distance using Mantel tests.…”
Section: Methodsmentioning
confidence: 71%
“…Populations of coastal Douglas fir are not differentiated strongly from one another using allozymes (Li and Adams 1989), RAPDs (Aagaard et al 1998), or chloroplast and nuclear microsatellites (Viard et al 2001;Krutovsky et al 2009). The average level of population differentiation (G ST ) was $0.02-0.07 in all studies, with Li and Adams (1989) noting weak to moderate (r , 0.30) isolation-by-distance effects in the coastal populations.…”
Section: Methodsmentioning
confidence: 99%
“…Allozyme and microsattelite markers used to study the population structure of coastal Douglas-fir have shown that there is weak differentiation between the coastal populations (KRUTOVSKY et al, 2009). Had the trials examined here been established on harsher sites in New Zealand, particularly with a lot of wind exposure or where rainfall is more limited, it is possible that the genotype x environment interaction found would have increased.…”
Section: G X E and Snc Resistancementioning
confidence: 99%
“…Had the trials examined here been established on harsher sites in New Zealand, particularly with a lot of wind exposure or where rainfall is more limited, it is possible that the genotype x environment interaction found would have increased. The evidence of low differentiation from KRUTOVSKY et al (2009) suggests that there may not be value in doing so. It would, however, be productive to integrate data from these studies in New Zealand with those from (DEAN, 2007;DEAN, 2008;DEAN, 2009) or similar studies, to determine whether similar levels of provenance x environment effects exist.…”
Section: G X E and Snc Resistancementioning
confidence: 99%